2017
DOI: 10.4172/pharmaceutical-sciences.1000235
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Cardiotoxicity: A Review on Major Side-effect of Doxorubicin

Abstract: Mobaraki, et al.: Molecular Mechanisms of Doxorubicin-induced CardiotoxicityDoxorubicin is among the most widely used drugs for the treatment of both adult and child cancers. Doxorubicin is the major cause of chemotherapy-induced cardiotoxicity that is dose limiting for the treatment of cancer. Many studies have explored pathophysiology and mechanisms of doxorubicininduced cardiotoxicity. Cellular and animal experiments proposed that doxorubicin-induced cardiotoxicity mechanism is multifactorial. Oxidative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 60 publications
0
40
0
1
Order By: Relevance
“…Doxorubicin-Induced Cardiotoxicity: Rats were randomly divided into eight groups of ten animals in each. A series of a single intraperitoneal dose of doxorubicin (13,14,15,16,17,18,19 and 20 mg/kg) was injected to each animal after a 16 h fast. All animals were sacrificed by cervical dislocation three days after the administration of doxorubicin.…”
Section: Treatment Of Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Doxorubicin-Induced Cardiotoxicity: Rats were randomly divided into eight groups of ten animals in each. A series of a single intraperitoneal dose of doxorubicin (13,14,15,16,17,18,19 and 20 mg/kg) was injected to each animal after a 16 h fast. All animals were sacrificed by cervical dislocation three days after the administration of doxorubicin.…”
Section: Treatment Of Animalsmentioning
confidence: 99%
“…The present study was conducted to determine the dose-dependent cardiotoxic changes observed in doxorubicin-induced acute cardiotoxicity because the acute cardiotoxicity has a higher prevalence than the chronic cardiotoxicity 13 . Although, the chronic cardiotoxicity is dose-dependent, and the extent of damage depends on the cumulative dosage, the acute cardiotoxicity can be evident even with the administration of one dose of doxorubicin.…”
Section: Table 1: Effect Of Different Doses Of Doxorubicin On Serum Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are several cellular pathways involved in DOX induce cardiotoxicity such as release of vasoactive substances, mitochondrial deteriorations, lipid peroxidation and depletion of the cellular antioxidants such as glutathione. As ROS liberation plays an essential role in the DOX induced cardiotoxicity we and other researchers focused on the potential involvement of ROS in DOX induced cardiotoxicity [2,3,4,6,33] ; Article no. JPRI.48804 effects as cardiotoxicity which may be exaggerated to reach heart failure major and the most serious adverse effect of DOX which limit its clinical usefulness.…”
Section: Photomicrograph Of Myocardium Section Of a Rat After 48 Hrsmentioning
confidence: 99%
“…It has been reported that the cardiomyopathy and congestive heart failure after treatment with DOX is dosedependent [4,5]. Doxorubicin induces its cardiotoxicity by many mechanisms such as DNA and RNA damages, induction of oxidative stress through liberation of reactive oxygen specious, lipid peroxidation, increase the endoplasmic reticulum-mediated apoptosis, inhibition of autophagy and interference with of calcium homeostasis [2,6]. In addition, DOX metabolism produces superoxide anion and hydroxyl radical which lead to toxic manifestation in the cellular membrane of the normal cells.…”
Section: Introductionmentioning
confidence: 99%